K.H. Hasyim Asy'ari's Thoughts and its Relevance in Modern Islamic Education - Masruri, Masruri (Program Pascasarjana Pendidikan Islam Universitas Islam Darul Ulum Lamongan, 2024)
This research is intended to examine Hasyim Asy'ari's thoughts on the book Adabul Al-'Ālim Wa Al-Muta'allim Fī Mā Yaḥtāju Ilaihi Al-Muta'allim Fi Ahwal Ta'limihi Wa Ma Yatawaqqafu' 'Alaihi Al Mu'allim Fi Maqāmātihi Ta 'limihi Chapters 1 and 2 are relevant to modern education today. This type of qualitative research uses data collection techniques from books, journals, the web and others. The focus of this research is on figures that are relevant to current developments.